The Utilization of Memrise in Arabic Language Learning with Blended Learning Method - Aulia Subita; Mohammad Ahsanuddin (Universitas Muhammadiyah Yogyakarta, 2022)
Rapid development of technology influences learning process where online learning has replaced the traditional learning. However, because of the numerous problems posed by this transition, the learning process has changed to use blended learning by utilizing technological media. This research aims to describe the utilization of Memrise in Arabic language learning with blended learning method and to describe the obstacles in utilizing Memrise in learning process. This study employs a descriptive qualitative methodology with Miles-Huberman’s data analysis techniques. This study revealed that the process of utilizing Memrise in Arabic language learning using the blended learning method is conducted through several stages, which are preparing the media, face-to-face learning, and online learning. The obstacles in utilizing Memrise in learning process faced by the teacher and students, including inadequate facilities, extra payment for more features and less flexible quizzes.